(untitled) (Indian Journal of Animal Production and Management, 2024)
An experiment was conducted to study the effect of dietary supplementation of Moringa oleifera leaf meal (MLM) on production economics of Vanaraja laying hens. One hundred twenty (120), Vanaraja laying hens of 24 weeks of age were selected at random and divided into four groups of 30 each with three replicates of 10 in each group in a complete randomized design. Four experimental diets were fed to birds in which T1 (control-antibiotic powder – oxytetracycline @ 50g/ quintal) and in rest of the 3 treatment groups T2, T3 and T4, the birds were fed with MLM at levels of 0.25, 0.5 and 1.0% of feed, respectively. The feed consumption per bird (kg), cost of feed per egg produced, egg production per bird, cost of feed per egg produced (Rs) for the experimental duration of 25-36 weeks was calculated. There was no significant difference (p> 0.05) between the treatment groups in terms of production economic parameters during the entire period of experiment. All the birds gained body weight during the experimental period indicating that there was a positive energy balance. From the present study, it is concluded that MLM up to 1% level in the diet of Vanaraja laying hens was at par with the antibiotic supplementation without affecting the production economics.